2012
DOI: 10.1063/1.3679404
|View full text |Cite
|
Sign up to set email alerts
|

Reorientation dynamics of nanoconfined water: Power-law decay, hydrogen-bond jumps, and test of a two-state model

Abstract: The reorientation dynamics of water confined within nanoscale, hydrophilic silica pores are investigated using molecular dynamics simulations. The effect of surface hydrogen-bonding and electrostatic interactions are examined by comparing with both a silica pore with no charges (representing hydrophobic confinement) and bulk water. The OH reorientation in water is found to slow significantly in hydrophilic confinement compared to bulk water, and is well-described by a power-law decay extending beyond one nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
92
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(105 citation statements)
references
References 45 publications
12
92
1
Order By: Relevance
“…[16][17][18][19][20][21][22] In addition, previous studies including ours have shown that the confined water molecules are composed of at least two phases, such as a bulk-like water phase having hydration structure and an adsorbed water phase near the surfaces at an ambient temperature, and two-state or core/shell models have been applied. 14,15,30,31 These results suggest that a bulk-like hydration water phase and an adsorbed water phase are ascribed to water that freezes and does not freeze below freezing point in both 1 nm-and 10 nm-scale environments, respectively.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22] In addition, previous studies including ours have shown that the confined water molecules are composed of at least two phases, such as a bulk-like water phase having hydration structure and an adsorbed water phase near the surfaces at an ambient temperature, and two-state or core/shell models have been applied. 14,15,30,31 These results suggest that a bulk-like hydration water phase and an adsorbed water phase are ascribed to water that freezes and does not freeze below freezing point in both 1 nm-and 10 nm-scale environments, respectively.…”
Section: Resultsmentioning
confidence: 82%
“…[5][6][7][8] Over the past decades, the effects of confinement in mesoporous silica materials with 1 nm-scale spaces on microscopic properties of water molecules have been examined using experimental and theoretical methods. [9][10][11][12][13][14][15] These studies have clarified that the hydrogen bonding structures of water molecules near the pore surface are distorted and perturbed due to water-surface interactions or topological effects even at ambient temperatures. Moreover, since water confined in 1 nmscale spaces adopts a supercooled state below the freezing point of bulk water, microscopic properties and liquid/solid phase transition of confined water have been investigated in a considerably low temperature region.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39] In addition, the reorientational and diffusional dynamics are slowed, often dramatically. 10,[39][40][41][42][43][44][45][46][47][48][49] The effect of nanoscale confinement on water is more limited to the interfacial region compared to other liquids despite the fact that it is a networked liquid. 22,39,46,47 This can primarily be attributed to the absence in water of steric effects that propagate the constraints of the confining surface to larger distances in other liquids.…”
Section: Introductionmentioning
confidence: 99%
“…42,[64][65][66] This dynamical heterogeneity is characteristic of water in nanoscale confinement, including water in silica nanopores. 67 As an extension of the study of the relaxation of "neat" water nanopools in RMs, it is natural to ask how the presence of peptide solvated in the RM will impact the orientational dynamics of water. In particular, when comparing the rotational relaxation of water in the absence and presence of peptide, is it possible to distinguish differences that can be attributed to water in direct interaction with the peptide?…”
Section: E Influence Of Solvated Peptide On the Orientational Dynamimentioning
confidence: 99%